2010
DOI: 10.1002/humu.21298
|View full text |Cite
|
Sign up to set email alerts
|

Deletions of the RUNX2 gene are present in about 10% of individuals with cleidocranial dysplasia

Abstract: Cleidocranial Dysplasia (CCD) is an autosomal dominant skeletal disorder characterized by hypoplastic or absent clavicles, increased head circumference, large fontanels, dental anomalies, and short stature. Hand malformations are also common. Mutations in RUNX2 cause CCD, but are not identified in all CCD patients. In this study we screened 135 unrelated patients with the clinical diagnosis of CCD for RUNX2 mutations by sequencing analysis and demonstrated 82 mutations 48 of which were novel. By quantitative P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 16 publications
2
61
0
Order By: Relevance
“…Copy number analyses on genomic DNA were performed on ABI Prism 7900HT System as described previously [13]. All primer sequences are available on request.…”
Section: Mutation Screeningmentioning
confidence: 99%
“…Copy number analyses on genomic DNA were performed on ABI Prism 7900HT System as described previously [13]. All primer sequences are available on request.…”
Section: Mutation Screeningmentioning
confidence: 99%
“…They did not establish a clear correlation between clinical features and genotype, the phenotypes of all patients analyzed falling within the range of variation described in CCD without an effect related to the length of the predicted protein. Furthermore, Ott et al, (2010) indicated that heterozygous deletions or duplications affecting the RUNX2 gene may be present in about 10% of all patients with a clinical diagnosis of CCD which corresponds to 26% of individuals with normal results on sequencing analysis. Accordingly, Lee et al, (2008) suggested that the deletion/duplication assay can improve the molecular diagnosis of CCD and likely change the statistics of molecular mechanism of this disease.…”
Section: P1mentioning
confidence: 99%
“…Accordingly, Lee et al, (2008) suggested that the deletion/duplication assay can improve the molecular diagnosis of CCD and likely change the statistics of molecular mechanism of this disease. Additionally, Ott et al, (2010) suggested that screening for intragenic deletions and duplications by qPCR or MLPA should be considered for patients with CCD phenotype in whom DNA sequencing does not reveal a causative RUNX2 mutation.…”
Section: P1mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that loss-offunction mutations in a single allele of the CBFA1 gene encoding runt-related transcription factor 2 (RUNX2), which is an osteoblastogenic master transcription factor, are detected in 60% of the CCD patients as a consequence of impaired osteoblast-mediated ossification (3)(4)(5)(6)(7)(8). However, the genetic origin of 40% of the CCD patients is still unknown (8), suggesting that mutations in other genes can lead to this syndrome.…”
Section: Introductionmentioning
confidence: 99%